Penggunaan Fintech Bagi Pelaku Usaha Mikro dan Menengah (UMKM) dalam Mengembangkan Usaha di Pesisir Pantai Kota Bengkulu - Fisabilillah, Fahri; Murwani, Anis Endang Sri; Yanto, Yanto; Dianthi, Martha Heriniazwi (Translitera : Jurnal Kajian Komunikasi dan Studi Media, 2025)
Advances in digital technology in Indonesia have driven significant transformation in the financial sector, one of which is through financial technology (fintech). This study aims to explore the role of fintech in supporting the development of Micro, Small, and Medium Enterprises (MSMEs) in the coastal area of Bengkulu City. The research uses a qualitative approach with observation, interviews, and documentation methods. The theory used is the public relations role theory by Cutlip, Center, and Broom (2006), which includes public opinion evaluation, organizational policy identification, and public relations activity planning. The results of the study indicate that fintech provides various benefits, such as ease of access to financial services, efficiency in financial management, and increased competitiveness of MSMEs. Solutions such as digital wallets, QR code-based payments, and microfinance help business actors overcome limitations in access to conventional banking. However, challenges such as low digital literacy, limited access to technology, high transaction costs, and inadequate internet infrastructure remain major obstacles.